Association Between Family History of Malignant Neoplasms and Clinicopathological Features of Breast Cancer Patients - CAO Xinhua (Zhongliu Fangzhi Yanjiu, 2020)
Objective To investigate the association between family history of malignant neoplasms (MN-FH) and clinicopathological characteristics of patients with breast cancer. Methods We analyzed retrospectively the clinical data of 417 breast cancer patients in Zhong Da Hospital from January 2016 to December 2018. Patients were grouped based on MN-FH or non-MN-FH. The clinical and pathological features of the patients were analyzed by χ2 test. Results Among 417 breast cancer patients, 67(16.1%) cases had MN-FH. Compared with non-MN-FH group, MN-FH group had higher proportion of vascular thrombosis (P=0.046), lymph node metastasis (P=0.023), ER negative (P=0.025), PR negative (P=0.031) and HER2 positive (P=0.041). In the further subgroup analysis, compared with non-MN-FH patients, patients with breast cancer history had higher tumor stage (P=0.011) and the tumors were more likely to be triple-negative and HER2-positive (P=0.010). Breast cancer patients with family history of other malignant tumors had higher proportion of vascular thrombosis (P=0.036) and lymph node metastasis (P=0.034). Conclusion Breast cancer patients with MN-FH have higher degree than non-MN-FH patients. For people with MN-FH, physical examination is very important.